ASSESSMENT OF NUTRITIONAL STATUS OF HEMODIALYSIS PATIENTS RECOVERED FROM COVID-19 (The Research of Medical Science Review, 2025)
Malnutrition is commonly present in patients relying on hemodialysis. The aim of this study to assess the nutritional status of hemodialysis patients that have recovered from Covid-19 and to identify the factors associated with malnutrition in hemodialysis patients. Present study is a descriptive cross-sectional study. Settings include in this study were Ittefaq Hospital Lahore, Abdullah General Hospital Okara and District Head Quarter’s Hospital Okara, Pakistan. This data interprets that 68% are moderate malnourish, 30% are mild and 1.7% is suffering severe malnutrition. This study concluded that majority HDP suffered with mild to moderate malnutrition and malnutrition is associated with other factors like chronic complications, food intake, gender, BMI and other.